Commandants, officers and exceptions in the regiments of the National Guard of the countryside (province of Buenos Aires, 1852-1880) (Quinto Sol, 2017)
In this paper, we study the internal dynamic about the regiments and battalions of the National Guard of Buenos Aires province countryside. We analyse the conformation of the body of officers and the negotiation that commandants started with the inhabitants of the districts assigned to them at the moment of making recruitment registers and designating members of the contingents. We prove that although the National Guard was created from provisions of the National and provincial state, the consolidation and effective operation of the institution in the countryside and the frontier were produced from the activities that commanders developed within the jurisdictions they were in charge of.
Keywords: National Guard; commandants; body of officers; exceptions; province of Buenos Aires